Counterproductive Academic Behaviors and Academic Performance: A Meta-Analysis and a Path Analysis Model - Salgado, Jesús F.; Cuadrado, Dámaris; Moscoso, Silvia (Frontiers in Psychology, 2022)
Counterproductive academic behaviors (CAB) are a complex phenomenon that affects academic institutions in multiple geographical areas with different cultures, values, and social norms. The high incidence of CAB causes problems of critical importance that transcend the educational domain. The current study aims to contribute to the knowledge of the CAB consequences by focusing on its impact on academic performance (AP). For this purpose, a meta-analysis was conducted in order to examine the relationship between CAB, its facets, and AP. The results show that overall CAB and students’ performance are negatively related with a true effect size of ρ = -.40 (K = 231, N = 127,269). Particularly, absenteeism appeared to be the facet most strongly related to AP (ρ = -.48, K = 117, N = 69,453). A meta-analytic path analysis model was carried out in order to test the predictive validity of CAB, students’ personality characteristics, and intelligence on AP. Results show that conscientiousness and cognitive intelligence have a negative relationship with CAB (β = -.28 and β = -.20, respectively) and that conscientiousness, openness to experience, intelligence, and CAB can explain 58% of AP true variance. Meta-analyses of moderator variables and hierarchical meta-analyses are also presented. The implications for research and practice are discussed at the end.